2021
DOI: 10.1136/jitc-2020-001335
|View full text |Cite
|
Sign up to set email alerts
|

Druggable epigenetic suppression of interferon-induced chemokine expression linked toMYCNamplification in neuroblastoma

Abstract: BackgroundAmplification of the MYCN oncogene is a molecular hallmark of aggressive neuroblastoma (NB), a childhood cancer of the sympathetic nervous system. There is evidence that MYCN promotes a non-inflamed and T-cell infiltration-poor (‘cold’) tumor microenvironment (TME) by suppressing interferon signaling. This may explain, at least in part, why patients with NB seem to have little benefit from single-agent immune checkpoint blockade (ICB) therapy. Targeting MYCN or its effectors could be a strategy to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…G9a inhibition is required for transcriptional responses to IFN-γ and histone mark changes at CXCL9 and CXCL10 gene loci in MYCN-positive NB cells. These findings highlight the important role of G9a in high-risk, MYCN-expressing, NB [73].…”
Section: G9a and Neuroblastomamentioning
confidence: 56%
“…G9a inhibition is required for transcriptional responses to IFN-γ and histone mark changes at CXCL9 and CXCL10 gene loci in MYCN-positive NB cells. These findings highlight the important role of G9a in high-risk, MYCN-expressing, NB [73].…”
Section: G9a and Neuroblastomamentioning
confidence: 56%
“…MYCN also downregulates DKK3 expression and activates the Wnt/β-catenin signaling pathway at the transcriptional level, boosting the development of B-ALL ( 69 ). Meanwhile, MYCN apparently decreases the interferon signaling, promoting a non-inflamed and T-cell infiltration-poor (“cool”) tumor microenvironment ( 70 ). In the classification rule based on the MCFS results, HDGF targeted by cg18593717 was an important locus, which exhibited a lower methylation level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, G9a is inversely associated with CD8 + T cell infiltration in melanoma and colon cancer. Moreover, it can inhibit the activated of Th1 cytokines/chemokines ( 32 , 33 ). Further investigation revealed that Ga9 induces chromatin variability in chemokine-related genes, involved in homing of intratumoral effector lymphocytes and natural killer cells ( 34 ).…”
Section: Classification and Biological Functions Of Histone Methyltra...mentioning
confidence: 99%